Analysis of the association of VIPR2 polymorphisms with susceptibility to schizophrenia. (30th July 2016) - Jin, Chunhui; Zhou, Zhenhe; Li, Weidong; Zhang, Fuquan; Yuan, Jianmin; Liu, Xiaowei; Cheng, Zaohuo
Abstract: In a previous study, we confirmed that copy number variants (CNVs) within the VIPR2 gene in Han Chinese individuals exhibit an increased risk of schizophrenia (SCZ). Herein, we further analyzed the association of eight tagged single nucleotide polymorphisms (tagSNPs) from the HapMap database with SCZ susceptibility. However, we found no significant positive signals in overall association and haplotypes analyses. Interestingly, significant SNP-SNP interaction signals associated with the risk of SCZ were observed using Multifactor Dimensionality Reduction (MDR) analysis. Furthermore, the 'CC' genotype of the VIPR2 gene was nominally associated with an increased risk of SCZ in male patients. Highlights: We investigated the association of VIPR2 variants with the risk of schizophrenia. No significant association was observed in overall samples. SNP-SNP interaction signals were significantly associated with the risk of SCZ. The SNP rs3812311 was nominally associated with the risk of schizophrenia in male samples.